EVALUASI KUAT TEKAN BETON DENGAN VARIASI SUBSTITUSI ABU BATU SEBAGAI UPAYA PEMANFAATAN LIMBAH MATERIAL: EVALUASI KUAT TEKAN BETON DENGAN VARIASI SUBSTITUSI ABU BATU SEBAGAI UPAYA PEMANFAATAN LIMBAH MATERIAL - Larassati, Dian Sukma; Setiawan, Adi; Wiguna, Edo; Hudaya, Diah Wulansari; Imansyah, Salmaa R. N; Purwanto; Yuono, Sukma Setyo (Politeknik Negeri Semarang, 2025)
Infrastructure development in Indonesia is growing rapidly, necessitating economical and environmentally friendly building materials. Concrete is a key construction material, but the cement-making process produces significant carbon emissions. To reduce environmental impacts, one method is to use industrial waste, such as rock ash, as a substitute for sand in concrete mixes. This study aimed to examine the effect of rock ash use on the compressive strength of K-225 quality concrete after 28 days. Five mixtures were tested with ratios of rock ash ranging from 0% to 100% replacing sand. The results showed that none of the mixtures achieved the desired compressive strength of 225 kg/cm². However, the mixture with 50% rock ash provided the best compressive strength of 194.385 kg/cm² with the lowest standard deviation (8.648 kg/cm²), indicating consistent quality. The decrease in compressive strength at higher rock ash levels was due to the presence of fine particles and silt exceeding the maximum limit. The study concluded that fly ash can be used as a sand substitute up to 50% of the time, provided its quality meets technical standards. The use of fly ash can help save costs, conserve natural resources, and support sustainable development.